Usability of Gazelle Form Beech Tree (Fagus Orientalis L.) leaves as an alternative roughage source in dairy cattle: using in vitro gas production method - Kaya , A (Adem); Kaya , A (Ali); Kaya , H; Macit , M; Palangi, V (Journal of the Hellenic Veterinary Medical Society, 2025)
An evaluation was conducted to determine whether beech tree leaves can be used as an alternative forage source for dairy cattle in TMR rations and their anti-methanogenic properties. The TMR rations were altered by substituting 0, 25, 50, 75, and 100% of gazelle form beech leaf for dry meadow grass. As a result, significant differences were found between experimental groups in terms of estimated parameters, total gas, dry matter, organic matter, NDF, ADF, protein digestion values, TUFA, acetic, propionic, and butyric acid values (P<0.05). As a result of substituting beech leaves for the entire dry meadow grass, in vitro TDMD, MPP, MPSE, TDD values improved and decreased propionic and butyric acid levels. Using beech leaves as a roughage source reduced in vitro methane production numerically. Therefore, it was concluded that tree leaves in the form of gazelle can be used as a source of roughage in dairy cattle TMR instead of the whole dry meadow grass, and further studies are needed to clarify this issue.